Determinan Kurangnya Minat Menabung di Bank Syariah - Purwati, Deni (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to identify and analyze the factors that influence the lack of interest in saving at Islamic banks. This research is a type of qualitative research, by taking informants from the research area, namely Pemalang Regency. The data in this study are primary data and data collection techniques by conducting interviews, documentation and observation. The research was conducted by gathering information regarding the factors that influence the lack of interest in saving at Islamic banks. Triangulation techniques were also carried out to ensure data validity. The results of the study found the causes of the lack of public interest in saving in Islamic banks, namely consideration of the benefits obtained, salaries received through conventional banks, lack of marketing strategies carried out by Islamic banks, lack of understanding of Sharia, the influence of culture and habits, convenience, closure of one of the Islamic banks, dubious sharia compliance implemented by Islamic banks and lack of security. The results of this study are expected to contribute to Islamic banks in Indonesia in formulating their marketing strategies to attract public attention to saving at Islamic banks so as to increase the market share of Islamic banks in the future.